User Responses Of The Development Of Language Laboratory System - Monalisa Pasaribu; Ike Fitriyaningsih; Sopian Manurung; Jane Mitaria Sinambela; Anjelin Hutauruk; David Muliadi Butar-Butar (International Journal of Education, Information Technology, and Others, 2020)
The data collection of room loans, inventory, and books is an important activity as a means of documentation at the language laboratory of Del Institute of Technology. Using manual process of the borrowing and data collection, possibility of data loss may occur. Moreover, it is also laborious and inefficient in terms of time. An information system is designed to improve the existing manual system in a computerized way that it can be accessed via desktop or mobile. Using agile software in the development the information system, the application can provide complete and efficient loan information stored in a database server. Based on the user responses, the system is built in a more effective, simpler, faster, and a more structurized way.